Солнечные элементы на основе тандемных гетероструктур GaAs–InGaAs–AlGaAs - Krukovsky, S. I.; Nikolaenko, Yu. E. (PE "Politekhperiodika", Book and Journal Publishers, 2003)
The paper reports on the fabrication and investigation of tandem solar cells based on GaAs–InGaAs–AlGaAs with an active area of 0.93 cm². A tunnel junction is used to connect the upper (AlGaAs) and lower (InGaAs) cells of the tandem solar element. Under spectral conditions AM 1.5 (1 sun), the measured short-circuit current density and open-circuit voltage reached 14.2–15.1 mA/cm² and 2.35–2.43 V, respectively, while the efficiency was 26.4–30.1%.